Need analysis for the development of mobile app glossary of terms in Islamic banking and finance - Dollah, Nafi@Hanafi; Md Ghalib, Mohd. Feham; Hassan, Rusni; Omar, Zakaria; Zakaria, Abdul Wahab; Sahrir, Muhammad Sabri (PC Culture Housing Society, 2015)
Newer development in mobile technology allows the use of hand phone which can be extended not only to communication but also to other personal life styles such as digital references in a form of dictionary or encyclopaedia, to the users for just in time, just enough, and just for me access of information. One of the areas that received vast attention nowadays by educationists and learners alike is the area of Islamic banking and finance. The expansion of Islamic banking practices through various local financial institutions leads to the need in understanding the terminologies used in the industry in “just-in-time” manner due to the dynamism of the field itself. In view of this scenario, the present research seeks to shed some light using a workable model for developing a purposeful mobile Islamic banking terminology glossary app in a more convenient way and made it operational via devices such as iPhone, iPad or any Android-based smart gadgets. It further explored the prototype development and its implementations for mobile accessibility by providing multilingual glossary of Islamic banking and finance terminologies (Malay-Arabic-English). The translation of specific terms from any academic field needs collaboration between experts both from the language and subject domains. This paper reports the findings of the need analysis stage, inclusive of mapping users’ device type, Internet accessibility, reasons for owning mobile devices, delivery and user interface, and preferred features to be embedded in the mobile app.